Pengembangan Cerita Wayang Suluh tentang Pentingnya Pendidikan di Kabupaten Waykanan - Damiri, Dharlinda Suri; Ginarso, Adi; Wicaksono, Andri; Harjanto, Ambyah (Lentera: Jurnal Ilmiah Kependidikan, 2025)
This study aims to develop a local culture–based learning medium through the Wayang Suluh performance themed “The Importance of Education in Way Kanan Regency, Lampung.” The background of the research highlights the low public awareness of the importance of education due to cultural factors, economic constraints, and the lack of contextual educational media. The research employed a Research and Development (R&D) method with the ADDIE development model. The medium was developed through local potential analysis, design, product creation, expert validation, student trials, and field testing. The results show that the medium is highly feasible for use and received positive responses from the community across different educational backgrounds. Wayang Suluh has proven to be effective as an inclusive and communicative educational tool while reinforcing local values. The implications of the research include strengthening character education in schools, integrating cultural elements into the formal curriculum, providing a foundation for local wisdom–based education policies, and promoting literacy movements rooted in regional arts and history. This medium also has the potential to be replicated in other regions as an educational strategy and a means of cultural preservation.